Collaborative Governance dalam Program “EPPSON” sebagai Perwujudan Smart City di Kota Surakarta - Hilmy Yahya; Sudarmo Sudarmo (Jurnal Mahasiswa Wacana Publik, 2022)
The all-digital era like now encourages countries to immediately make changes towards digitalization, including Indonesia. Where the Indonesian government is launching the “100 smart cities” program, one of which is Surakarta. The city government of Surakarta itself has several excellent programs, one of which is the EPPSON program, which was created with a vision to increase PAD and provide convenience for the community. In realizing the program, the government collaborates with several stakeholders or is called collaborative governance. So that researchers are interested in researching the collaboration model carried out with Ansell and Gash's theory and finding out the effectiveness of the collaboration that has been carried out using the basic 5 theories of the effectiveness of collaborative governance belonging to experts which are elaborated into 7 indicators. The method used is descriptive qualitative by using primary and secondary data sources. In his findings, it was found that collaboration had been carried out well according to Ansell and Gash's model and for effectiveness, most of it had been met and there was one indicator that had not been met and had to be corrected immediately, namely the sharing of information in collaboration forums.